PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 029 SUNGAI AGAS KECAMATAN KUBU - Jumiati Jumiati '; Lazim N Lazim N '; Zulkifli Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research is motivated by lowmathematics learning outcomes ofstudents, with an average grade of 56.5. While the completeness criteria Minimumvalue (KKM) Mathematics is 65 Among students who totaled 20 people only 7students who achieve KKM with classical completeness 35%. This research isClassroom Action Research (CAR) conducted aims to improve learning outcomesMathematics Elementary School fourth grade students Agas River 029 withRealistic Mathematics learning approach. Data collection instruments in thisthesis is the sheet activities of teachers and students and learning outcomes. Thisthesis presents the results obtained by studying the average learning outcomesbefore action 56.5 9.54% increase to 62 in cycle I. In the second cycle increasedby 34.27% to an average of 76. activities of teachers in the first cycle the firstmeeting of the percentage 64.2% obtained with either category, the secondmeeting had become 71.4%. Furthermore, the first meeting of the second cycleactivity score of 85.71% of teachers increased by either category once, at thesecond meeting increased to 92.8% with bik category once. The results of the dataanalysis of student activity in the first cycle to 53.5% with good category, 64.2%in the second meeting the students already understand this cycle of learningactivities with the application of learning approaches PMR. And the second cyclestudents activity score increased 82.1% excellent category. At the second meetingincreased to 92.8% with the excellent category. The results of the study at 029River Elementary School fourth grade Segajah prove that the application of arealistic approach to mathematics learning can improve learning outcomes Math029 fourth grade students of SDN Agas River.Keywords: Realistic Approach To Mathematics, Mathematics Learning Outcomes